Crushed Entities: Rejection, Compassion, Work, and Inexistence in Trump Reopens an Old Wound for Haitians, We Must not Forget Detained Migrant Children and Without Inspection - Morales Quant, Jaime Andrés (2020)
From discourses from philosophy, literary criticism, and the study of emotions, I explore images of immigrants, mainly Haitians, in the United States. I start from a textual corpus that is made up of two opinion articles and a story written by Edwidge Danticat: Trump Reopens an Old Wound for Haitians (2017), We Must not Forget Detained Migrant Children (2018a) y Without Inspection (2018b). My proposal involves the identification, schematization, and analysis of four characterizations that Danticat poses around immigrants: a) being beaten and rejected by presidents, US immigration centers, media, banks, filmmakers, music producers; b) agents and recipients of compassion; c) poor and exploited individuals, driven by the need to survive, and not by the imperative of performance, suggested by Han for the contemporary world of work (2012); d) invisible and non-existent entities in life, and blurred at the moment of their death.